Pediatric apheresis with a novel apheresis device with electronic interface control. Issue 4 (6th August 2012) - Sörensen, Jan; Jarisch, Andrea; Smorta, Carmelo; Köhl, Ulrike; Bader, Peter; Seifried, Erhard; Bönig, Halvard
<x xml:space="preserve">Abstract</x> BACKGROUND: Cancer in children, and specifically cancer requiring autologous stem cell transplantation, is rare. As a consequence, though, experience with pediatric stem cell apheresis collections is limited. Challenges of apheresis in small children (<20 kg) include small total blood volume, issues with venous access, concerns about tolerable anticoagulant doses, and limitations in product volumes that can safely be collected. STUDY DESIGN AND METHODS: This article presents a small series of autologous "stem cell" apheresis procedures in infants and toddlers weighing between 5.5 and 20 kg, the first ones performed with a novel leukapheresis device (Spectra Optia MNC v.3.0, Terumo BCT) to be reported. Some features of the system are described that can be used to achieve favorable apheresis outcomes in small children. RESULTS: Apheresis procedures were uneventful and successful with similar extraction efficiencies (median preapheresis collection efficiency [CE2], 36%) as in adult patients. At 58%, platelet attrition was considerable. CONCLUSION: Our data indicate that stem cell apheresis with the Spectra Optia MNC v.3.0 in very small donors is feasible, safe, and associated with very small product volumes.